2003
DOI: 10.1016/s0168-6496(02)00462-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recovery of environmental DNA for expression cloning by indirect extraction methods

Abstract: Using direct and cell extraction-based (indirect) isolation methods, DNA was obtained from environmental samples with largely differing characteristics (loam soil, sand soil, sediment, activated sludge, and compost) and evaluated with respect to the comprised bacterial diversity and its suitability for expression cloning in Escherichia coli. Indirect DNA extraction methods yielded 10 to 100-fold lower amounts of DNA than direct procedures, but the bacterial diversity of DNA recovered by indirect means was dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 49 publications
(74 reference statements)
4
132
1
10
Order By: Relevance
“…DNA extraction from sediments DNA extraction was performed according to a protocol described by Lueders et al (2004) and Gabor et al (2003). Briefly, 0.2 ml of B1:1 mixed 0.1 mm and 0.5 mm silica beads and 700 ml PTNbuffer (120 mM NaPO 4 , 125 mM TRIS, 25 mM NaCl, pH 8) were added to 0.5 cm 3 sediment.…”
Section: Enumeration Of Virus-like Particles (Vlps)mentioning
confidence: 99%
“…DNA extraction from sediments DNA extraction was performed according to a protocol described by Lueders et al (2004) and Gabor et al (2003). Briefly, 0.2 ml of B1:1 mixed 0.1 mm and 0.5 mm silica beads and 700 ml PTNbuffer (120 mM NaPO 4 , 125 mM TRIS, 25 mM NaCl, pH 8) were added to 0.5 cm 3 sediment.…”
Section: Enumeration Of Virus-like Particles (Vlps)mentioning
confidence: 99%
“…Martin-Laurent et al 2001;Luna et al 2006); however, other studies did not identify such a relationship (e.g. Gabor et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…In the indirect extraction method, the microbial cells are separated before cell lysis and DNA extraction and purification, resulting in less non-bacterial DNA (Osborn and Smith 2005). Comparative benchmarking of direct and indirect extraction methods showed that the indirect method yielded 10-to 100-fold lower amounts of DNA than did direct procedures, but revealed a much higher bacterial diversity (Gabor, de Vries et al 2003). The disadvantages of indirect methods are the longer processing time and lower DNA yields.…”
Section: Dna Extractionmentioning
confidence: 99%